George Palmer Putnam papers - Putnam, George Palmer, 1814-1872.; Carey, Henry Charles, 1793-1879.
Published proceedings (1868) of a meeting chaired by Putnam that resulted in the establishment of the International Copyright Association. Contains 24 handwritten letters (tipped in) addressed to Putnam and relating to copyright matters; pamphlet (87 pages) on international copyright by Henry Charles Carey; and an annotated printed catalog of autograph letters for sale by G. P. Putnam & Co., in 1858.
Publisher.
Collection material in English.
Keywords: G. P. Putnam & Co; International Copyright Association; Autographs -- Collections; Copyright, International; Publishers